Visitor

2016-04-25 02:29:14

#1

If we have the following geometric progression, (a_{n}), with n from **N** and the properties:

a_{4} - a_{2} = 6

a_{3} - a_{1} = 3

then a_{1} and *q* are:

1) a_{1} = -1, q = 3

2) a_{1} = 3, q = 1/2

3) a_{1} = 2, q = -2

4) a_{1} =1, q = 2

a

a

then a

1) a

2) a

3) a

4) a

Visitor

2016-04-24 15:00:17

#2

Let's write like this:

a_{1} = a

a_{2} = aq

a_{3} = aq^{2}

a_{4} = aq^{3}

a_{4} - a_{2} = aq^{3}-aq=aq(q^{2} - 1)

a_{3} - a_{1} = a(q^{2} - 1)

a

a

a

a

a

a

Visitor

2016-04-24 15:33:12

#3

So, the last option is good

It is not mandatory to be logged in on this forum but it is nice to have an account. You can ask about mathematics just with your name and your email.

This maths forum is one of the easiest forums to use it.